Dried blood spots to characterize mercury speciation and exposure in a Colombian artisanal and small-scale gold mining community. (March 2021) - Santa-Rios, Andrea; Barst, Benjamin D.; Tejeda-Benitez, Lesly; Palacios-Torres, Yuber; Baumgartner, Jill; Basu, Niladri
Abstract: The artisanal and small-scale gold mining (ASGM) sector uses the most mercury (Hg) worldwide. Despite health concerns associated with high Hg exposures in these communities, ASGM sites are often situated in resource limited and remote regions which challenge traditional human biomonitoring approaches. To help overcome such challenges, here we report on the development of a high-quality method to characterize chemical speciation of Hg in dried blood spots (DBS), and then apply this method to assess Hg exposures in people sampled from an ASGM community (Pueblito Mejia) and a nearby town (Barranco de Loba) in Colombia. We collected DBS and urine samples from 35 individuals in 2018, and used these to assess occupational (DBS inorganic Hg (InHg) and urine total Hg (THg) measures) and environmental (DBS methylmercury (MeHg) measures) exposure of participants to different forms of Hg. The accuracy and precision of the DBS-based measures generally met assay performance guideline. In study participants, the mean concentrations of DBS MeHg, InHg, and THg, and urine THg were 1.9, 4.1, 6.0, and 3.1 μg/L, respectively. For 37% of the participants, DBS THg values exceeded the 5 μg/L 'alert level' proposed by the German HBM Commission. About 60% of the blood Hg was in the InHg form thus exemplifying a need to speciate Hg in blood sampled from ASGM sites to better understand the contributions of environmental and occupational exposure sources. This study demonstrates the feasibility of using DBS for Hg speciation exposure assessments in remote and resource-limited areas such as ASGM communities. Graphical abstract: Image 1 Highlights: ASGM communities are exposed to different forms of mercury. Dried blood spots are an ethical, economic, and efficient way to sample blood. Chemical species of mercury were measured in dried blood spots. Methods applied in Colombian population in resource limited and remote region.